Kajian Strategi Pembelajaran Efisiensi Energi Berdasarkan Konsep Termodinamika di Sekolah Dasar: Systematic Literature Review - Easter Merryetta Simanjuntak; Fazrilina Afriani; Septiani Zulfa Saidah; Afridha Laily Alindra (STKIP Subang, 2026)
Conventional science education at the elementary school level often reduces the essence of energy efficiency to mere theoretical memorization, which triggers acute misconceptions about basic thermodynamic concepts. To address this issue, this study aims to critically examine the effectiveness of various thermodynamics-based energy efficiency learning strategies. The method used is a Systematic Literature Review (SLR) adopting the PRISMA guidelines. Thematic analysis was conducted with the subject of study focusing on elementary school students, sourced from 15 articles meeting the inclusion criteria in the Scopus database (2020-2026). The results of the literature synthesis prove that passive didactic approaches have failed to build energy literacy. Meaningful concept internalization is significantly achieved through contextual interventions, integration of local wisdom, STEM-PjBL approaches, eco-theology, and micro-empirical experiments. These strategies are proven to deconstruct misconceptions regarding temperature and heat, and transform the abstraction of physical laws into practical literacy. In conclusion, this study asserts that pedagogical transformation in science learning is an absolute intervention to produce a generation critically aware of energy conservation in their surrounding environment.